Physical activity modulates inhibitory control: EEG insights from P300 and theta oscillations - Liu, Liqing; Hao, Yan; Zhao, Zhihui; Liu, Qing (Frontiers in Human Neuroscience, 2025)
IntroductionPrevious studies have mainly focused on the effects of exercise on inhibitory control, but the impact of daily physical activity has not been thoroughly examined. This study aims to investigate how physical activity affects inhibitory control functions and the underlying neural mechanisms involved.MethodsWe examined 36 adults, divided into two groups based on their daily physical activity levels: a high physical activity level (HPAL) group consisting of 18 participants and a low physical activity level (LPAL) group, also with 18 participants. Physical activity levels were measured using the International Physical Activity Scale. Neural dynamics were recorded through electroencephalography (EEG) as participants performed a modified Flanker task to assess their inhibitory control abilities.ResultsOur results indicate that physical activity has a significant impact on inhibitory control. Individuals with high levels of physical activity showed significantly larger P300 amplitudes compared to those in the low physical activity group. Additionally, we observed enhanced theta and alpha oscillatory power in the HPAL group when compared to the LPAL group. Furthermore, we found a positive association between higher levels of physical activity among participants and increased amplitudes of P300 as well as theta oscillations.DiscussionOur findings provide electrophysiological evidence that physical activity strengthens inhibitory control through the enhancement of conflict-related P300 responses and synchronization of prefrontal theta activity, suggesting improved neural efficiency in managing cognitive interference.